Intestinal Growth in Glucagon Receptor Knockout Mice Is Not Associated With the Formation of AOM/DSS-Induced Tumors - Hunt, Jenna Elizabeth; Yassin, Mohammad; Olsen, Jørgen; Hartmann, Bolette; Holst, Jens Juul; Kissow, Hannelouise (Frontiers in Endocrinology, 2021)
Treatment with exogenous GLP-2 has been shown to accelerate the growth of intestinal adenomas and adenocarcinomas in experimental models of colonic neoplasia. However, the role of endogenous GLP-2 in tumor promotion is less well known. Mice with a global deletion of the glucagon receptor (Gcgr-/-) display an increase in circulating GLP-1 and GLP-2. Due to the intestinotrophic nature of GLP-2, we hypothesized that Gcgr-/- mice would be more susceptible to colonic dysplasia in a model of inflammation-induced colonic carcinogenesis. Female Gcgr-/- mice were first characterized for GLP-2 secretion and in a subsequent study were given a single injection with the carcinogen azoxymethane (7.5 mg/kg) and treated with dextran sodium sulfate (DSS) (3%) for 6 days (n=19 and 9). A cohort of animals (n=4) received a colonoscopy 12 days following DSS treatment and all animals were sacrificed after six weeks. Disruption of glucagon receptor signaling led to GLP-2 production in the pancreas of Gcgr-/- mice which coincided with an increase in small intestinal (p<0.0001) and colonic (p<0.0489) weight. Increased villus height was recorded in the jejunum and ileum (p<0.05 and p<0.001) and crypt depth was increased in the duodenum and jejunum (p=0.0197 and p=0.0334). Disruption of glucagon receptor signaling did not affect body weight during AOM/DSS treatment, neither did it affect inflammatory score assessed during colonoscopy or the number of large and small adenomas present at the end of the study period. In conclusion, despite the increased GLP-2 produced by the pancreas of Gcgr-/- mice, these mice were not more susceptible to AOM/DSS-induced tumors.